2022
DOI: 10.1186/s12913-022-08967-3
|View full text |Cite
|
Sign up to set email alerts
|

Providing sexual and reproductive health services to migrants in Southern Sweden: a qualitative exploration of healthcare providers’ experiences

Abstract: Background While a large body of research has focused on the challenges experienced by healthcare staff when providing sexual and reproductive health services, little attention has been paid to the ways healthcare providers navigate these challenges. This study examined healthcare providers’ accounts of encounters when providing sexual and reproductive health (SRH) services to migrants in Southern Sweden. It sought to examine challenges and dilemmas experienced by healthcare providers, strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Mpofu’s (2018) research on health and wellbeing among religious adherents in Zimbabwe found that religious beliefs potentially expose women and children to health risks. They potentially pose barriers to services such as contraception and abortion and limit discussions about SRH (Amroussia, 2022; Mpofu, 2018; Mpofu et al, 2014). Our study underscores the need for culturally safe and religiously sensitive health education and services that respect religious beliefs and ensure comprehensive access to SRHRs (Mpofu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mpofu’s (2018) research on health and wellbeing among religious adherents in Zimbabwe found that religious beliefs potentially expose women and children to health risks. They potentially pose barriers to services such as contraception and abortion and limit discussions about SRH (Amroussia, 2022; Mpofu, 2018; Mpofu et al, 2014). Our study underscores the need for culturally safe and religiously sensitive health education and services that respect religious beliefs and ensure comprehensive access to SRHRs (Mpofu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At the exosystem level, healthcare systems, extended family, and government policies play a role in shaping MRY's approach to SRHR, while the macrosystem level encompasses attitudes, ideologies, culture, and religion, all of which influence MRY's reproductive health decisions in Australia (Napier-Raman et al, 2023). Mpofu (2018) and Amroussia et al (2022) agree on the significant impact religion can have on MRY's SRHR beliefs and behaviours (Amroussia, 2022;Mpofu, 2018). Cultural concentration, in which migrants maintain a connection to their culture while adapting to the host country, can bring both opportunities and challenges for MRY in renegotiating relationships and family structures in a new cultural context (Dune et al, 2017;Rawson & Liamputtong, 2010;Saleem et al, 2017;Villa-Torres & Svanemyr, BARRIERS TO SRHR IN MIGRANT AND REFUGEE YOUTH 7 2015).…”
Section: Barriers To Srhr In Migrant and Refugee Youthmentioning
confidence: 99%
“…In particular, methods, tools, and materials documents generally either implicitly or specifically targeted young migrants’ SRHR, which might reflect efforts to improve practitioners’ cultural competency. Health practitioners have previously identified lack of cultural competency, knowledge and skills as potential barriers in their encounters with migrant patients [ 25 , 26 ]. Access to continued education and professional development for professionals is included in one of the NAP’s prioritised areas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to recognize that these challenges occur across all cultures and settings. Amroussia et al’s (2022) study emphasises the importance of avoiding othering young migrants in discourse surrounding HRV and oppression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is a body of literature documenting the SRH needs of women refugees and migrants in humanitarian settings around the world (8)(9)(10)(11), there is insufficient evidence about migrant women's and girl's SRH needs during the transit phase of migration. This lack, in turn, makes it challenging to develop effective interventions that can support their SRH throughout their journey.…”
mentioning
confidence: 99%